The Botany, Chemistry, Pharmacological and Therapeutic Application of Oxalis Corniculata Linn– A Review - Hemant Badwaik; Mukesh Kumar Singh; Deepa Thakur; Tapan Kumar Giri; D.K Tripathi (International Journal of Phytomedicine, 2011)
Oxalis corniculata Linn. is an endangered and medicinally important plant indigenous to tropical and subtropical regions of the world. Its medicinal usage is reported in Indian pharmaceutical codex, the Chinese, British and the American pharmacopoeias and in different traditional system of medicines such as Ayurveda, Unani and Siddha. The review reveals that wide ranges of phytochemical constituents have been isolated from the plant like flavanoids, tannins, phytosterols, phenol, glycoseides, fatty acids, galactoglycerolipid and volatile oil. The leaves contain flavonoids, iso vitexine and vitexine-2”- O- beta – D- glucopyrunoside. It is rich source of essential fatty acids like palmitic acid, oleic, linoleic, linolenic and stearic acids and it possesses important activities like Antioxidant, Anticancer, anthelmintic, Anti-inflammatory, Analgesic, Steroidogenic, Antimicrobial, Antiamoebic, Antifungal, Astringent, Depurative, Diuretic, Emmenagogue, Febrifuge, Cardio relaxan, stomachic and Styptic have also been reported. These repots are very encouraging and indicate that herb should be studied more expensively for its therapeutic benefits. This article briefly reviews the botany, pharmacology, biochemistry and therapeutic application of the plant. This is an attempt to compile and document information on different aspects of Oxalis corniculata and highlight the need for research and development.